The state as cultural practice - Bevir, Mark.; Rhodes, R. A. W. (Oxford : Oxford University Press, 2010)
'The State as Cultural Practice' offers an original theory of the state. In place of the institutional state, Bevir and Rhodes argue for 'the stateless state', or for a focus on the contingent beliefs and practices of individuals. In short, they put the people back into the study of the state.
Description based on print version record.
Includes bibliographical references and index.
Keywords: State, The; State, The -- Social aspects